Exploring Microbial Resource of Different Rhizocompartments of Dominant Plants Along the Salinity Gradient Around the Hypersaline Lake Ejinur - Luo, Junqing; Zhang, Zhechao; Hou, Yazhou; Diao, Fengwei; Hao, Baihui; Bao, Zhihua; Wang, Lixin; Guo, Wei (Frontiers in Microbiology, 2021)
Lake littoral zones can also be regarded as another extremely hypersaline environment due to hypersaline properties of salt lakes. In this study, high-throughput sequencing technique was used to analyze bacteria and fungi from different rhizocompartments (rhizosphere and endosphere) of four dominant plants along the salinity gradient in the littoral zones of Ejinur Salt Lake. The study found that microbial α-diversity did not increase with the decrease of salinity, indicating that salinity was not the main factor on the effect of microbial diversity. Distance-based redundancy analysis and regression analysis were used to further reveal the relationship between microorganisms from different rhizocompartments and plant species and soil physicochemical properties. Bacteria and fungi in the rhizosphere and endosphere were the most significantly affected by SO42-, SOC, HCO3- and SOC, respectively. Correlation network analysis revealed the potential role of microorganisms in different root compartments on the regulation of salt stress through synergistic and antagonistic interactions. LEfSe analysis further indicated dominant microbial taxa in different rhizocompartments had a positive response to plants, such as, Marinobacter, Palleronia, Arthrobacter and Penicillium. This study was of great significance and practical value for understanding salt environments around salt lakes to excavate the potential microbial resources.